DIGITAL TRANSFORMATION IN SHARIA COOPERATIVE MANAGEMENT: IMPLEMENTATION, OPPORTUNITIES, AND CHALLENGES IN THE MODERN DIGITAL ERA - Fitri Nur Latifah; Franciska Marta Oftariana; Kafita Luluk Anjani (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study examines the implementation, opportunities, and challenges of digital transformation in the management of sharia cooperatives, aiming to enhance their relevance and competitiveness in the modern digital era. Digitalization is essential for improving financial services, operational efficiency, and member engagement while maintaining compliance with sharia principles. Method: A qualitative approach was employed, utilizing literature reviews and case studies to analyze digital transformation initiatives within sharia cooperatives. The study explored the integration of sharia-based financial applications, online member management systems, and collaborations with sharia fintech as key aspects of digital adoption. Results: The findings indicate that digital transformation in sharia cooperatives offers significant opportunities, including improved financial inclusion, service innovation, and enhanced competitiveness. However, challenges such as limited technological infrastructure, low digital literacy, high investment costs, and data security risks pose significant barriers to implementation. Strategic planning, human resource development, and multi-stakeholder collaboration are critical to overcoming these obstacles. Novelty: This study highlights the intersection of digital transformation and Islamic financial principles, emphasizing a strategic framework for integrating digital tools while maintaining sharia compliance. The research contributes to the discourse on Islamic financial digitalization by proposing an adaptive model that aligns technological advancements with ethical and religious considerations, ensuring sustainable growth for sharia cooperatives.